Acceleration performance results of the SN nodal transport solvers in MOSASAUR code system for lead-based reactor cores - Wang, Bo; Xu, Zhitao; Wang, Lianjie; Zhang, Bin; Lou, Lei; Zhao, Chen (Frontiers in Nuclear Engineering, 2024)
To address the efficiency bottleneck encountered in reactor design calculations for the newly developed lead-based reactor neutronics analysis code system MOSASAUR, we recently developed acceleration functions based on various coarse-mesh finite difference (CMFD) methods and spatial domain decomposition parallel algorithm. However, the applicability of these improvements to different lead-based reactors remains to be analyzed. This work collected and established core models for various types of lead-based reactor. Based on different SN nodal transport solvers, we analyzed the acceleration performance of different CMFD methods, different CPU cores, and the combination of CMFD and parallel calculation. The results indicated that the impact of different CMFD acceleration or parallel acceleration on the calculation accuracy was negligible; the rCMFD method had good stability and convergence rate, achieving speedup of several to dozens; parallel efficiency was related to the number of meshes, and for large reactor cores, superlinear speedup was achieved with 200 CPU cores; rCMFD and parallel computing could achieve combined speedup, with 200 cores achieving speedup of hundreds to thousands, typically completing a reactor core transport calculation in 1 minute.